Selected Papers on Contemporary Economic Problems / Presented at the Econometric Society European Meetings, Athens, 1979 - Charatsis E. G (The Athens School Of Economics & Business Science, 1982)
Preface, Introduction, Optimal Control and Econometric Systems, Problems in Aggregation and Autoregression, Estimating Methods, Consumer Demand Systems and Related Topics, Investment Functions, Production Functions and Factor Demand, Author and Subject Index.